2017
DOI: 10.4081/ija.2017.949
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation of Slovenian sweet potato varieties (Ipomoea batatas) and effect of different growing media on their agronomic and nutritional traits

Abstract: The objectives of the present study were firstly to analyse the genetic relatedness among three Slovenian sweet potato varieties; and secondly to assess the effects of different growing media on selected agronomic and nutritional traits of these varieties. Tubers of three varieties (Lučka, Janja, Martina) with different skin/flesh colour were produced in planters under glasshouse conditions in five different growing media (perlite, peat, expanded clay, vermiculite, garden soil) from prior raised seedlings. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…The levels of vitamin C in raw roots in our study were higher than a range of 13.7-23.5 mg/100 g reported in Slovenia (Sinkovič et al, 2017) but comparable to values reported in Tanzania of 273-303 mg/100 g for sweetpotato leaves (Mwanri et al, 2011).Vitamin C is highly susceptible to oxidation more so in aqueous solutions, oxidation being fueled by the presence of oxygen, metal ions such as iron and copper and high temperature (Akah & Onweluzo, 2014;Lee & Kader, 2000). Traditionally, leaves are boiled in water for more than 10 min.…”
Section: Vitamin C Content In Sweetpotato Productscontrasting
confidence: 93%
“…The levels of vitamin C in raw roots in our study were higher than a range of 13.7-23.5 mg/100 g reported in Slovenia (Sinkovič et al, 2017) but comparable to values reported in Tanzania of 273-303 mg/100 g for sweetpotato leaves (Mwanri et al, 2011).Vitamin C is highly susceptible to oxidation more so in aqueous solutions, oxidation being fueled by the presence of oxygen, metal ions such as iron and copper and high temperature (Akah & Onweluzo, 2014;Lee & Kader, 2000). Traditionally, leaves are boiled in water for more than 10 min.…”
Section: Vitamin C Content In Sweetpotato Productscontrasting
confidence: 93%
“…SSR (Simple Sequence Repeats) markers can potentially make a significant contribution to the genomics enabled improvement of grass pea. Compared to other agronomically important plant species, SSR markers are the most frequently employed to assess intra-and inter-specific genetic diversity and its genetic structure (Pipan and Meglič, 2019;Pipan et al, 2018;Sinkovič et al, 2017).…”
Section: Introductionmentioning
confidence: 99%